Recent advances in the development and evaluation of molecular diagnostics for Ebola virus disease. (3rd April 2019) - Tembo, John; Simulundu, Edgar; Changula, Katendi; Handley, Dale; Gilbert, Matthew; Chilufya, Moses; Asogun, Danny; Ansumana, Rashid; Kapata, Nathan; Ntoumi, Francine; Ippolito, Giuseppe; Zumla, Alimuddin; et al.
ABSTRACT: Introduction : The 2014-16 outbreak of ebola virus disease (EVD) in West Africa resulted in 11, 308 deaths. During the outbreak only 60% of patients were laboratory confirmed and global health authorities have identified the need for accurate and readily deployable molecular diagnostics as an important component of the ideal response to future outbreaks, to quickly identify and isolate patients. Areas covered : Currently PCR-based techniques and rapid diagnostic tests (RDTs) that detect antigens specific to EVD infections dominate the diagnostic landscape, but recent advances in biosensor technologies have led to novel approaches for the development of EVD diagnostics. This review summarises the literature and available performance data of currently available molecular diagnostics for ebolavirus, identifies knowledge gaps and maps out future priorities for research in this field. Expert opinion : While there are now a plethora of diagnostic tests for EVD at various stages of development, there is an acute need for studies to compare their clinical performance, but the sporadic nature of EVD outbreaks makes this extremely challenging, demanding pragmatic new modalities of research funding and ethical/institutional approval, to enable responsive research in outbreak settings. Retrospective head-to-head diagnostic comparisons could also be implemented using biobanked specimens, providing this can be done safely.